'From an Agro-Based to a Mineral Resources-Dependent Economy': A Critical Review of the Contribution of Mineral Resources to the Economic Development of Zimbabwe. Issue 1 (2nd January 2018) - Malinga, Wayne
Abstract: Once dubbed the food basket of Southern Africa in the 1990s by the Southern African Development Community (SADC), Zimbabwe, over the last two decades, has failed to live up to its name and reputation. An erratic land reform policy by the ZANU PF-led government marked the downfall of the agricultural sector. Commercial farming collapsed ushering in an era of semi-commercial farming and subsistence farming which did little to live up to the expectations of SADC and let alone its people. Once an agro-based economy, Zimbabwe started to show signs of collapse when it embroiled itself in continuous failure to feed its own people. The country has been marred by poverty and hunger. However, the discovery of minerals such as diamonds in Chiadzwa and gold marked a new era in the economic revival and resuscitation of Zimbabwe. Focus now shifted from an agricultural-based economy to a mineral resources-dependent economy. All of this was part of the efforts to revive an impoverished country. This article delves into this intriguing transition and whether mineral resources have been a viable option in reviving and resuscitating the Zimbabwean economy. It focuses on the reasons why the agricultural sector has failed under the ZANU PF-led government? This article unearths the linkages between natural resources and economic growth. It concludes that proper management of mineral resources can actually go a long way in addressing the economic development of Zimbabwe. To achieve this, there is a need for transparency and accountability in all involved stakeholders.